A Comparison of Frequency Domain Electro-Magnetometry, Electrical Resistivity Tomography and Borehole Temperatures to Assess the Presence of Ice in a Rock Glacier - Boaga, Jacopo; Phillips, Marcia; Noetzli, Jeannette; Haberkorn, Anna; Kenner, Robert; Bast, Alexander (Frontiers in Earth Science, 2020)
Alpine permafrost is currently warming, leading to changes such as active layer deepening and talik formation. Frequency domain electro-magnetometry (FDEM) measurements were tested as a simple and efficient method to investigate ground characteristics along two transects on the ice-rich Schafberg rock glacier in the Eastern Swiss Alps. The results were compared with electrical resistivity tomography (ERT) and ground temperature data acquired simultaneously in boreholes. FDEM provides information on the electrical properties of the ground, allowing to investigate ground-ice distribution. Our device allowed measurements to a depth of around 7 m. In ice-rich permafrost, FDEM can provide an approximation of the active layer thickness, and ice-free zones within the permafrost such as intra-permafrost taliks can be identified. This rapidly applicable geophysical method can be used to monitor ground ice distribution easily and efficiently, making it an ideal complement to borehole temperature data, which only provide point information and are costly to install and maintain. At the Schafberg site the three methods FDEM, electrical resistivity tomography and borehole temperature measurements provided similar results, with regard to active layer thickness and the presence of unfrozen zones within the ice-rich permafrost.